Хронотоп та жанрова специфіка дилогії «Шлях невідомого» і «Дім над кручею» Ігоря Качуровського - Жигун, С. (Літературознавчі обрії. Праці молодих учених, 2010)
The article deals with the chronotop of dilogy «The road of the unknown» and «The house on the steep bank» by I. Kachurovsky as a factor of the artistic unity of the work and genre specificity. The core of «The road of the unknown» is a chronotop of the road on which various meetings are waiting for the hero during his travel to the native land. Linear adventurous time predominates. But in «The house on the steep bank» this type of time interlaces with the cyclic idyllic time. The volume of chronotop, its ability to incorporate the smaller chronotops, establish complicated relations between them and some other characteristics make it possible to determine the genre of the dilogy as a novel in short stories, and genre variety – as an adventurous-intellectual one.